Perancangan Madrasah Aliyah Kejuruan Boarding School Khusus Perempuan dengan Pendekatan Arsitektur Metafora - Iqlima Nabila Khairunnisa; Wahyuni Zahra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Education creates an optimal learning environment and an active learning process for students to develop their potential and help them achieve goals in improving knowledge and morals, as well as building children's personalities. Lack of educational facilities and difficulty managing free time are also problems for teenagers in channeling their talents and interests and preparing for a better future. Madrasah Aliyah Vocational Boarding School as an alternative school has an optimal environment for character education. The aim of this research is to design a Madrasah Aliyah Vocational Boarding School that can meet educational needs, a good learning environment, security and safety, as well as several supporting architectural factors and elements by applying metaphorical architectural aspects. The research method is carried out using qualitative methods, which can be collected by collecting data from literature studies, case studies or similar themes, then direct observation of educational activities. The application of a design with a metaphorical architectural theme, which uses the basic shape of a rose, is expected to visually illustrate the function of the building. Thus, observers and building users are expected to be able to clearly obtain ideas and impressions of the activities taking place within it through the shape of the building mass and facade.